Safeguarding “The Frog Pond”: London West and the Resistance to Municipal Amalgamation 1883–1897 - Stott, Greg (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2000)
The London, Ontario, suburb of London West (1874 to 1897) provides an example of a community that strove to maintain its municipal autonomy. Composed of independent wage earners, artisans, and small-business owners, London West cultivated a sense of identity separate from that of its neighbouring city. While a devastating flood in 1883 devalued property and greatly soured relations between the village and London, it buttressed community unity in London West. The flood similarly caused the villagers to insist upon the maintenance of certain controls in order to assure the security of their property and families in their negotiations with the city for amalgamation. After several protracted periods of discussions, the village tenaciously held out against the city until 1897, when ratepayers had little alternative but to accept London's less than satisfactory conditions. While the ultimate decision to join the city in 1897 was based more upon the village's dismal financial situation, London West's protracted resistance to municipal amalgamation indicates that nineteenth-century suburbs in Ontario were complex communities in their own right and not simply undifferentiated adjuncts that craved amalgamation with their urban neighbours.